Pengaruh Digital Leadership dan AI Integration Terhadap Innovation Capabilities Pada PT Eigerindo Multi Produk Industri (Eiger) (Studi Kuantitatif pada Karyawan PT Eigerindo Multi Produk Industri) - Almaira Sarah Junjunan; Nisa Febrianti; Sarah Mutia Azahra; Megha Sakova (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the effect of Digital leadership and AI Integration on Innovation Capabilities at PT Eigerindo Multi Produk Industri (EIGER). A quantitative causal-associative design was employed, with cross-sectional survey data collected from 31 employees selected through purposive sampling via an online Google Form questionnaire. Data were analyzed using multiple linear regression. Classical assumption tests indicated the model met the assumptions of normality (Shapiro-Wilk W = 0.955, p = 0.216), no multicollinearity (VIF = 1.430), and homoscedasticity (Glejser test, p > 0.05). The regression equation obtained was Y = 0.948 + 0.367X1 + 0.422X2. Partial t-tests showed that Digital leadership significantly and positively affected Innovation Capabilities (t = 2.773, p = 0.010), as did AI Integration (t = 2.632, p = 0.014). The simultaneous F-test confirmed that both variables jointly and significantly influenced Innovation Capabilities (F = 16.181, p = 0.00002), explaining 53.6% of its variance (R² = 0.536). However, reliability testing showed Cronbach's Alpha values below the ideal threshold of 0.70 for all three variables, largely attributable to the small sample size (n = 31), so the findings should be interpreted as exploratory and warrant replication with a larger sample and a refined instrument.